2005
DOI: 10.3200/jmbr.37.3.231-238
|View full text |Cite
|
Sign up to set email alerts
|

Support for an Explanation of the Guidance Effect in Motor Skill Learning

Abstract: ABSTRACT. The authors investigated whether the knowledge of results (KR) schedule influences the extent to which intrinsic feedback is noticed and used. Fifty-six participants received KR that was either delayed over 2 trials (Delay-2) or provided directly after each trial (Delay-0) during 160 trials of an unfamiliar aiming task. No-KR retention tests were given after 80 trials and 1 min and 24 hr after the end of acquisition. After retention, all participants were questioned about their use of intrinsic feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 31 publications
2
41
0
5
Order By: Relevance
“…In adults, frequent extrinsic feedback is thought to reduce reliance on intrinsic feedback and decrease the overall information-processing demands during practice trials. Subsequently, motor learning research suggests that faded and reduced extrinsic feedback is preferable in adults to engage active problem-solving mechanisms and improve skill retention over time (Anderson, Magill, Sekiya, & Ryan, 2005;Winstein & Schmidt, 1990). However, research suggests that typical children use feedback in a manner different from adults and may require longer periods of practice with more frequent feedback to retain new motor skills (Goh, Kantak, & Sullivan, 2012;Sullivan, Kantak, & Burtner, 2008).…”
Section: Child-focused Interventionsmentioning
confidence: 99%
“…In adults, frequent extrinsic feedback is thought to reduce reliance on intrinsic feedback and decrease the overall information-processing demands during practice trials. Subsequently, motor learning research suggests that faded and reduced extrinsic feedback is preferable in adults to engage active problem-solving mechanisms and improve skill retention over time (Anderson, Magill, Sekiya, & Ryan, 2005;Winstein & Schmidt, 1990). However, research suggests that typical children use feedback in a manner different from adults and may require longer periods of practice with more frequent feedback to retain new motor skills (Goh, Kantak, & Sullivan, 2012;Sullivan, Kantak, & Burtner, 2008).…”
Section: Child-focused Interventionsmentioning
confidence: 99%
“…Questions 1-8 were ranked on a 4-point Likert Scale: not at all (1), rudimentary (2), good (3), excellent (4). Questions 9 and 10 were ranked on a 5-point Likert Scale: very pleasant (1), pleasant (2), neutral (3), unpleasant (4), very unpleasant (5).…”
Section: Questionnairementioning
confidence: 99%
“…Furthermore, subsequent research is recommended to examine how much sonification feedback is optimal for rehabilitating participants gait. Investigating the optimal feedback frequency schedule is crucial as previous researchers suggested that too much or too little feedback could be detrimental to performance [1,37,38]. Subsequent investigations will implement retention tests to determine if any gait alterations, due to sonification, persist in the absence of feedback.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Los aprendices ponen más atención de cerca a sus sensaciones propioceptivas y exploran más la realimentación intrínseca disponible, cuando la realimentación extrínseca es demorada. Tal vez el instante preciso de dar realimentación no es inmediatamente luego de haber realizado la práctica de la habilidad, pues aquí es indispensable que el practicante explore más su realimentación inherente disponible (Anderson, Magill, Sekiya y Ryan, 2005).…”
Section: Cuál Es El Momento Preciso Para Dar Realimentaciónunclassified